Pengaruh Iklan Dan Citra Merek Terhadap Kepuasan Konsumen (Studi Pada Konsumen sepeda Motor Honda PT Helmi Hendra Motor Maja Majalengka) (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2020)
This research is motivated by the problem of companies that still use print media to advertisegoods, while currently there is digital technology that is more efficient for advertising andbrand images. This study aims to determine the effect of advertising, brand image onconsumer satisfaction of Honda motorbikes at PT Helmi Hendra Motor Maja either partiallyor simultaneously, using descriptive and verifiative analysis approaches so as to increaseproduct sales and revenue. Testing instruments using validity and reliability tests with a litertscale. The analytical tool used in this research is the Classical Assumption test, theCoefficient of Determination and Multiple Linear Regression. While testing the hypothesisusing the t test for partial and f test for silmutan. It can be seen that advertising is in the goodcategory, brand image is in the good category, and customer satisfaction is in the highcategory. Partially that advertising has a significant effect on customer satisfaction, brandimage has a significant effect on customer satisfaction. Simultaneously, advertising and brandimage have a significant effect on customer satisfaction.